INVESTIGATION OF THE EFFECTS OF TOMATO JUICE SUPPLEMENT ON TSH, TESTOSTERONE AND INSULIN LEVELS IN ATHLETES - Pala, Ragıp; Şengün, Nezihe; Gür, Leyla Sultan (Ataturk Universitesi, 2020)
14 healthy male athletes, who were given tomato juice (TJ) supplements with aerobic exercise, had an average age of 20.21 ± 2.08 years, had a mean BMI of 20.98 ± 2.61, and exercised an average of 2.50 ± 1.83 years in color branches, were formed and their TSH, testosterone and insulin levels were analyzed. The data was analyzed with the SPSS package program and the tests used to compare the averages between the groups to reveal the difference before and after the exercises for 42 days. The compliance of the data to normal distribution was examined using the Shapiro-Wilk test. Those with normal distribution among the data were analyzed with the Dependent T test and those that did not show normal distribution were analyzed with the Wilcoxon test. Statistical significance was accepted as p<0.05. When the TSH levels of aerobic exercise and TJ supplementation were examined, it was found that there was not an increase between the control and TJ+exercise groups (p>0.05), however, there was an increase between control and aerobic exercise groups (p<0.05). When testosterone levels were examined, it was found that there was an increase between the control and TJ + Exercise groups (p<0.01), an increase between control and exercise (p<0.05), and a significant increase between TJ + exercise and exercise groups (p<0.001). When the insulin levels were examined, it was found statistically that there was an increase in TJ + Exercise and exercise groups compared to the control screen (p<0.001). As a result, aerobic exercise applications results in an increase in TSH, total testosterone and insulin levels in athletes. It is determined that TJ + exercise supplementation does not affect TSH levels but it increases total testosterone and insulin levels of athletes. © 2020, Ataturk Universitesi. All rights reserved.
SPORCULARDA DOMATES SUYU TAKVİYESİNİN TSH, TESTOSTERON VE İNSÜLİN DÜZEYLERİNE ETKİLERİNİN İNCELENMESİ
Keywords: Exercise; Insulin; Testosterone; Tomato juice; TSH